A method to derive surface thermophysical properties of asteroid (162173) Ryugu (1999JU3) from in-situ surface brightness temperature measurements. (15th September 2018) - Hamm, Maximilian; Grott, Matthias; Kührt, Ekkehard; Pelivan, Ivanka; Knollenberg, Jörg
Abstract: The MASCOT radiometer MARA on board the Hayabusa2 mission will measure surface brightness temperatures on the surface of asteroid (162173) Ryugu in six wavelength bands. Here we present a method to constrain surface thermophysical properties from MARA measurements. Moreover, uncertainties when determining surface thermal inertia as well as emissivity are estimated. Using data from all filters and assuming constant emissivity, thermal inertia of a homogeneous surface can be determined with an uncertainty range of 250 ± 16 Jm − 2 K − 1 s − 1 / 2, while the emissivity uncertainty is below 6%. Similar results are obtained if emissivity is allowed to vary as a function of wavelength and if the MARA channels with the best signal-to-noise ratio are used to constrain thermal inertia. If the observed surface is heterogeneous and two morphologically different units are present in the instrument's field of view, thermal inertia of the subunits can be retrieved independently if their contrast in terms of thermophysical properties is large enough. If, for example, the surface is covered by equal area fractions of fine-grained and coarse-grained material, then thermal inertia is found to be retrievable with uncertainties of 658 ± 78 and 54 ± 22 Jm − 2 K − 1 s − 1 / 2 for the coarse-grained and fine-grained fraction, respectively.